Expression, refolding and spectroscopic characterization of fibronectin type III (FnIII)-homology domains derived from human fibronectin leucine rich transmembrane protein (FLRT)-1, -2, and -3 - Yang,Lila; Hansen Falkesgaard,Maria; Thulstrup,Peter Waaben; Walmod,Peter Schledermann; Lo Leggio,Leila; Krighaar Rasmussen,Kim (PeerJ, 2017)
The fibronectin leucine rich transmembrane (FLRT) protein family consists in humans of 3 proteins, FLRT1, -2, and -3. The FLRT proteins contain two extracellular domains separated by an unstructured linker. The most membrane distal part is a leucine rich repeat (LRR) domain responsible for both cis- and trans-interactions, whereas the membrane proximal part is a fibronectin type III (FnIII) domain responsible for a cis-interaction with members of the fibroblast growth factor receptor 1 (FGFR1) family, which results in FGFR tyrosine kinase activation. Whereas the structures of FLRT LRR domains from various species have been determined, the expression and purification of recombinant FLRT FnIII domains, important steps for further structural and functional characterizations of the proteins, have not yet been described. Here we present a protocol for expressing recombinant FLRT-FnIII domains in inclusion bodies in Escherichia coli. His-tags permitted affinity purification of the domains, which subsequently were refolded on a Ni-NTA agarose column by reducing the concentration of urea. The refolding was confirmed by circular dichroism (CD) and 1H-NMR. By thermal unfolding experiments we show that a strand-strand cystine bridge has significant effect on the stability of the FLRT FnIII fold. We further show by Surface Plasmon Resonance that all three FnIII domains bind to FGFR1, and roughly estimate a Kd for each domain, all Kds being in the µM range.
Keywords: Inclusion bodies; Disulphide bridge; On-column refolding; Interaction; Stability; Fibroblast growth factor receptor; Fibronectin type III domains; Fibronectin leucine rich transmembrane protein